Ayat Hadits Sebagai Pedoman Pendidikan: Membentuk Etika dan Moral Mahasiswa - Aulia, Maulida; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research investigates the impact of selected Hadith verses on shaping the ethics and morals of university students. Focusing on the positive influence of these Hadiths, the study explores the concrete moral guidance provided and the diversity of effects on individuals. Through a qualitative approach involving in-depth interviews and quantitative analysis of survey data, the research reveals that the Hadiths significantly contribute to the moral development of students. Several key Hadiths were examined, such as the emphasis on the purity of the heart, the importance of honesty, the promotion of empathy, and the obligation to seek knowledge. The findings indicate a positive correlation between understanding and applying these Hadiths and the development of strong moral values. The diversity of individual responses showcases the varied impact of Hadiths, enriching the overall moral fabric within the university environment. The relevance of these Hadiths to students' daily lives is highlighted, emphasizing their application in navigating academic challenges and fostering positive interpersonal relationships. The study's implications for moral education programs in higher education institutions are discussed, emphasizing the need to integrate these Hadiths into the curriculum. Overall, this research contributes valuable insights into the role of Hadiths in shaping the ethical foundations of university students, paving the way for more effective moral education strategies in academic settings.